Negative coping styles among individuals with cannabis use disorder and non-users - Sadaf Ahsan; Farhana Sajjad Kiani; Rubina Hanif; Syeda Naila Andleeb (Journal of the Pakistan Medical Association, 2021)
Objectives: To investigate the differences in negative coping styles used by individuals with cannabis use disorder and non-users. Methods: The quantitative cross-sectional study was conducted from November, 2016 to August 2017 at Foundation University, Rawalpindi, Pakistan, and comprised individuals aged 15-34 years. Data was collected from drug rehabilitation and university students of Rawalpindi and Islamabad. The sample was divided into groups of cannabis users and non-users. Data was collected using the brief version of the Coping Orientation to Problems Experienced inventory and the Diagnostic and Statistical Manual of Mental Disorders version 5. Data was analysed using SPSS 21. Results: Of the 204 participants, 104(51%) were users with a mean age of 27±5.37 years and 100(49%) were non-users with a mean age of 25±5.65 years. The users scored higher at active avoidance coping compared to the non-users (p<0.05). The differences were non-significant in case of denial and religious coping (p>0.05). Active avoidance coping differed across individuals with mild, moderate and severe cannabis use disorder (p<0.05), while religious and denial coping did not (p>0.05). Conclusion: Active avoidance coping was found to be an important characteristic in relation Continuous...